Self-assembled chitosan nanoparticles for intranasal delivery of recombinant protein interleukin-17 receptor C (IL-17RC): preparation and evaluation in asthma mice. Issue 1 (1st January 2021) - Lv, Yongli; Zhang, Jianhua; Wang, Chaoying
ABSTRACT: Asthma is mentioned as a chronic airway inflammatory disease, whose pathogenesis is complicated. The promotion of inflammation in asthma by IL-17A and IL-17F has been confirmed. In addition to covalent homodimers, both cytokines are also able to form heterodimers, further inducing downstream pathways via binding to the IL-17RA and IL-17RC receptor complex. In recent years, IL-17RA and its signal transduction pathway have been extensively researched. IL-17RC, however, remains relatively unexplored. In the present study, we self-assembled chitosan (CS) nanoparticles for intranasal delivery of recombinant protein IL-17RC (rIL-17RC) and preliminarily investigated its effect on a murine model of allergic asthma induced by ovalbumin (OVA). rIL-17RC was produced by the prokaryotic expression system and encapsulated into the CS nanoparticles via ionic cross-linking technique. The results showed that CS-RC nanoparticles via intranasal intervention significantly caused inhibition of mucus secretion and airway inflammatory cell infiltration, and reduced IL-4, IL-17, IL-17F levels in BALF. Hence, delivering receptor proteins such as IL-17RC, through CS nanoparticles as a carrier, could be an attractive therapeutic intervention for asthma. Grafical abstract: uf0001